Exploring the local dispute resolution mechanisms and a disputant's perspectives concerning the Siete Pecados issue. - Tortola, Niezel Anen Tulanda
This study sought to explore the local dispute resolution mechanisms which can help address the Siete Pecados issue trhough looking into the perspective of a disputant concerning that issue. Specifically, the study tried to determine the level of awareness on the Siete Pecados issue of the community and the LGU. It also looked into the community cohesion utilizing the constructive variables of alienation, solidarity, social ties and sense of belonging. The study also tried to ascertain the forms of local dispute resolution mechanisms present in the community. It likewise sought the community and LGU's willingness to address the issue using the local disputte resolution mechanisms. The study as well as established the association of the research variables. One hundred forty-nine (149) respondents from four selected coastal barangays of Dumangas and one (1) local government official was selected through simple random sampling performed as the research respondents., A dichotomous scale marked by "yes" or "no" was utilized to measure the respondents' level of awareness on the Siete Pecados issue. On the other hand, a five-point Likert Scale was used to determine the respondents' level of community cohesion through the vairables of alienation, solidarity, social ties and sense of belonging; and also the respondents' level of willingness to address the issue using the local dispute resolution mechanisms. Moreover, a checklist was employed in order to establish the forms of local dispute resolution mechanisms present in Dumangas. Frequency Distribution, Qualitative Analysis and Descriptive Statistics were used to analyze the results of the study. The Spearman Rank-Order Coefficient was utilized to determine the association of the variables. Research results showed that there is a significant level of awareness both in the community and in LGU. The results also presented that alienation is low, solidarity, social ties and sense of belonging are moderately high which in sum fostered a cohesive community. Moreover, the results also provided that there are various forms of lcoal dispute resolution mechanisms being utilized in the community such as Dialogues, Agreements, Negotiations, Meetings, Legislations, Arbitration, Mediation, Seminar, resolution through Local Courts, and others which included in Lupon and Pagtilipon. The study also found out that the respondens are willing to address the issue using these dispute resolution mechanisms. The results fruther showed that there is a positive association between awareness and willingness, among willingness and solidarity, social ties and sense of belonging. However, there is a negative association between all other variables and alienation.